Islamic Values And Environmental Sustainability: An Islamic Perspective On Preserving Nature - Fakhri Fikri; Laode Arif Nugraha; Erni Haryanti (al-Afkar, Journal For Islamic Studies, 2026)
Islam offers a profound ethical framework for addressing the global environmental crisis through its core values of tauhid (divine unity), khalifah (stewardship), and maslahah (public welfare). This study examines how these Islamic principles guide ecological conservation and promote sustainable practices grounded in the Qur’an and Sunnah. By conducting a thematic literature review of classical Islamic texts and contemporary scholarship, the research highlights the religion’s emphasis on maintaining mizan (natural balance) and condemning israf (wastefulness). The findings reveal that Islamic teachings position environmental preservation as both a spiritual duty and a communal responsibility, urging moderation in resource use and advocating for justice in ecological interactions. Examples such as Indonesia’s green waqf initiatives and Morocco’s renewable energy projects illustrate the practical application of these values in modern sustainability efforts. However, challenges such as consumerism and lack of religiously-grounded environmental awareness hinder progress. The study concludes that integrating Islamic ethics into education, policy, and grassroots activism can empower Muslim communities to lead in global conservation. By framing environmentalism as worship, Islam provides a holistic paradigm for harmonizing human needs with planetary health, aligning with its vision of rahmatan lil ‘alamin (mercy to all creation).